O som da paisagem : pelas praças do centro da cidade de Vitória, ES - Zaganelli, Deborah Martins (2014)
Soundscape is the acoustic environment of a place and over time, it is observed how the sonority of cities are changing, along with its development. This dissertation aims to characterize the Soundscape of open spaces with public use of the foundational a